L’oralité dans Allah Superstar : représentations, tensions, traduction - Mevel, Pierre-Alexis (Canadian Association for Translation Studies, 2018)
This article examines the way in which banlieue French—a largely predominantly spoken linguistic variety—is used narratively and aesthetically in Y. B.’s novel Allah Superstar, and makes suggestions with regards to its English language translation. The article will answer the following questions: how is orality portrayed in writing in the novel? What are the ideological ramifications and what is at stake with the translation of these oral traits within written discourse? Allah Superstar, through its unusual narrative style, written as if it were the transcription of a spoken narrative, or of a stand-up comedy show, offers an ideal field of study for the representation of orality and of its translation. The novel’s narrator relies on several features of so-called banlieue French. The use of this variety naturally raises ideological issues, since the systematic use of a non-standard variety is unusual in writing, stretches the boundaries of the language (even more so in the case of French which is characterised by great levels of diamesic variation) and subverts it—sometimes literally, through the use of features such as verlan, sometimes more deeply albeit not less violently. This variety is characterised by a certain terminological fuzziness, which indicates a problem with its definition. The analysis of orality in Y. B.’s novel illustrates the tension inherent in banlieue and its literature: caught between the standard variety of the language and the conventions of writing on the one hand, and the necessity of pushing its boundaries to create a form of difference on the other, the author draws on non-standard linguistic resources and stretches its codes and norms to give rise to an étrangement which raises important issues for the translation process. We will then provide ways to apprehend the translation of the banlieue, which is both so close and yet so far, and of Y. B.’s novel and its narrator whose voice equivocates between familiarity and strangeness.